Evaluation of the anatomical variation in the nasal cavity and paranasal sinuses of patients with cleft lip and palate using cone beam computed tomography - Dedeoglu, N.; Altun, O.; Kucuk, E. B.; Altindis, S.; Hatunoglu, E. (Comenius Univ, 2016)
OBJECTIVE: The aim of this study was to evaluate the frequency of anatomical variation in nasal cavity and paranasal sinuses by comparing a unilateral cleft lip and palate (UCLP) group with a non-syndromic control group using cone beam computed tomography (CBCT). SUBJECTS AND METHODS: This study included 24 UCLP patients in the UCLP group and 24 non-syndromic patients in the control group. Coronal CBCT images were taken in all patients and were evaluated for anatomical variation. The measurements obtained in this study were analysed using chi-square and Fisher's exact tests to compare the two groups statistically. RESULTS: In the UCLP group, there were statistically lower frequencies of pterygoid process pneumatisation (p<0.05), higher wing pneumatisation (p<0.05), and sphenoid sinus over pneumatisation (p<0.05), and statistically higher frequencies of anterior nasal septa] deviation (p<0.05) compared to the control group. CONCLUSION: A higher incidence of anterior nasal septal deviation was found in UCLP patients compared to the patients in the control group. It is likely that for this reason, UCLP patients might be predisposed to sinusitis. In UCLP patients, the incidence of neurovascular structures in the sphenoid sinus was lower than that in non-syndromic control patients (Tab. 1, Fig. 6, Ref. 33). Text in PDF www.elis.sk.
Keywords: cleft lip and palate; paranasal sinus; anatomical variation; nasal cavity; cone beam computed tomography